Capital intelectual na indústria de private equity e venture capital: um estudo sob a ótica dos investidores institucionais e gestores de fundos - Ferreira, Paulo Luiz (2010)
Due to deep transformation in the society, economy and politics provided from new technology and globalization, the knowledge has been the most important resource in building value. Since then, the organizations started to have as a dominant factor in building economic result, the intellectual capital. Therefore, the managers need new methodology which can measure and manage intangible resources. The object of this research is the private equity and venture capital industry (PE/VC) in Brazil, that has invested in innovative companies based in the intensive use of the knowledge, thus, it should be relevant to have mechanism to measure and manage the intellectual capital. The main purpose of the research is to verify the practice and the adopted initiative to measure, manage and exposure the intellectual capital in PE/VC industry, under the institutional investor and fund managers‟ view and to compare with the theoretical reference. The research is of an exploratory kind and the data collection was done through a questionnaire which was answered by twenty PE/VC fund manager and seven institutional investors. Through the research, the importance of the intellectual capital measurement has been proved, as well as, its exposure. Nevertheless, although the importance of measurement has been recognized, very few people have practiced it. They claim that the investors market and regulators do not really require it added to a lack of a standard method usually accepted. It is the accountancy duty to develop or refine a suitable method that can be used by all companies. Regarding the exposure of the intellectual capital, the main reasons shown to not to expose is the lack of information to be exposed and the understanding that the secret is important for this sort of information